Efektivitas Permainan Ular Tangga dalam Meningkatkan Literasi Numerasi Anak Usia 5-6 Tahun di PAUD Mutiara Bunda Desa Jatisawit - Devvi Natasha; Mushoddik Mushoddik; Mufid Zaiq Ja’far; Ahmad Baihaqi Esaputra (Jurnal Nusantara Berbakti, 2024)
Numeracy literacy skills are children's abilities to utilize, convey, and apply various numbers, number symbols, graphs, charts, tables, and the like to solve problems in everyday situations. The lack of learning effectiveness in the modern era in children's learning can be caused by several things such as the lack of teacher creativity in teaching, inadequate facilities. The hope of this research is to explore how effective the snakes and ladders method is in improving numeracy literacy in children aged 5-6 years. This research was conducted at the Mutiara Bunda PAUD, Jatisawit Village. The method applied by the author in this study is a qualitative method by taking reference sources from books, articles, journals, and previous research. The findings of this study explain that the use of the snakes and ladders game method can develop the effectiveness of learning for early childhood and can improve literacy skills and numeracy skills in early childhood. Based on the analysis, the snakes and ladders game can help children to be more effective during the learning process and can help children to be more active, and can solve every problem that occurs in the learning process so that children will be more interested and motivated to learn.